2019
DOI: 10.3389/fonc.2019.00527
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Section Tumor Micro-Architecture Analysis by a Two-Dimensional Phasor-Based Approach Applied to Polarization-Dependent Second Harmonic Imaging

Abstract: Second Harmonic Generation (SHG) microscopy has gained much interest in the histopathology field since it allows label-free imaging of tissues simultaneously providing information on their morphology and on the collagen microarchitecture, thereby highlighting the onset of pathologies and diseases. A wide request of image analysis tools is growing, with the aim to increase the reliability of the analysis of the huge amount of acquired data and to assist pathologists in a user-independent way during their diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…The collagen, accounting for 70-80% of dry skin weight, is the main component of the extracellular matrix [29,30] and can be employed as an indicator in the process of dermal repair. Collagen imaging has been widely used in the transdermal movement of drugs in vivo [31], scar prognosis [32,33], and cancerous tissues [34,35]. This study showed that b-FGF accelerated collagen production by TMP imaging in vivo, which was consistent with the Masson staining results in vitro.…”
Section: Discussionsupporting
confidence: 80%
“…The collagen, accounting for 70-80% of dry skin weight, is the main component of the extracellular matrix [29,30] and can be employed as an indicator in the process of dermal repair. Collagen imaging has been widely used in the transdermal movement of drugs in vivo [31], scar prognosis [32,33], and cancerous tissues [34,35]. This study showed that b-FGF accelerated collagen production by TMP imaging in vivo, which was consistent with the Masson staining results in vitro.…”
Section: Discussionsupporting
confidence: 80%
“…The spatial arrangement of collagen in stroma has also been observed in breast cancer and liver metastasis tissue samples using second harmonic generation spectroscopy (Scodellaro et al, 2019;Wang et al, 2019). Collagen patterns are associated with degree of tumor invasiveness (Pankova et al, 2016;Provenzano et al, 2008).…”
Section: Collagenmentioning
confidence: 98%
“…Interestingly, analysis of the PSHG data has also been achieved through Fourier projection of the PSHG image stacks onto two phasor plots referred to as microscopic multiparametric analysis by phasor projection of PSHG (µMAPPS). This technique has been used to compare the ρ values of SHG data taken from biopsies of the left flank of mice days after implantation of melanoma [40], colon carcinoma and breast cancer cells [41].…”
Section: Applications Of Shg Microscopy For Determining the Ultrastructure Of Diseased Collagenous Tissues Polarization-in Shg Microscopymentioning
confidence: 99%